Experimental Study on Performance of Concrete Incorporated with Alccofine-1203 And Fly ASH - Mrs. A Kalyani; A Ashok; V Janakiraman; B Vignesh (International Journal of Scientific Research in Civil Engineering, 2022)
The main issue with cement manufacture is that a considerable amount of carbondioxide is released, which raises the temperature of the atmosphere, resulting in global warming. As a result, we need a long-term replacement of cement in concrete to address the problem of global warming caused by carbon dioxide emissions. Alccofine 1203 is a custom-made material generated by a controlled granulation process with a high glass content and strong reactivity. Concrete gets extraordinary strength at a young age due to the use of Alccofine material. In this experiment, alccofine was replaced for the weight of cement by 0 percent, 10%, 15%, 20%, and 25% of the time, respectively. Several criteria were studied at 7 and 28 days after curing, including workability of fresh concrete using a slump cone and a compaction factor test, compressive strength on concrete cubes, and split tensile strength on concrete cylinders. The concrete grade used was M30. The findings reveal that the Alccofine material increases concrete strength significantly up to a replacement level of 25%, beyond which the concrete's strength starts to decrease. Based on the increase in strength in the variation of concrete mix, it provides better performance, implying that the use of waste material as a mineral supplement for concrete should be promoted.
Keywords: Alccofine; Compressive Strength; Split Tensile Strength